2017
DOI: 10.1016/j.actbio.2016.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered tumoral microtissues recapitulate desmoplastic reaction of pancreatic cancer

Abstract: Tumor microenvironment is extremely complex and its organization is due to the interaction between different kind of cells and the extracellular matrix. Tissue engineering could give the answer to the increasing need of 3D culture model that better recapitulate the tumor features at cellular and extracellular level. We aimed in this work at developing a microtissue tumor model by mean of seeding together cancer cells and fibroblasts on gelatin microsphere in order to monitor the crosstalk between the two cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 76 publications
1
49
0
3
Order By: Relevance
“…Their method was advantageous due to the ability to form large-sized spheroids within 24 h, control the tumor cell composition and density, and mimic the TME. Recently, Brancato et al confirmed the 3D model consistency with an in vivo setting, using biodegradable microcarriers (made of gelatin) in a spinner flask bioreactor [ 80 ]. In their system, pancreatic cancer cells were co-cultured with cancer-associated fibroblast, resulting in the formation of human pancreatic ductal adenocarcinoma microtissues.…”
Section: Tumor-microenvironment Interactions: 2d Vs 3dmentioning
confidence: 99%
“…Their method was advantageous due to the ability to form large-sized spheroids within 24 h, control the tumor cell composition and density, and mimic the TME. Recently, Brancato et al confirmed the 3D model consistency with an in vivo setting, using biodegradable microcarriers (made of gelatin) in a spinner flask bioreactor [ 80 ]. In their system, pancreatic cancer cells were co-cultured with cancer-associated fibroblast, resulting in the formation of human pancreatic ductal adenocarcinoma microtissues.…”
Section: Tumor-microenvironment Interactions: 2d Vs 3dmentioning
confidence: 99%
“…Other researchers reported the anti-fibrotic properties of EGCG in endometriosis (Matsuzaki & Darcha, 2014). Here, we analyzed the ECM remodeling, in particular, the collagen deposition of the auto-produced lamina propria before and after EGCG treatment by combining MPM with SHG imaging (Brancato et al, 2017;Imparato et al, 2017) and PSR staining. CAD analysis demonstrated the changes of collagen microstructure with a slight decrease of the total collagen found in the EGCG-treated samples (14.2 ± 0.08 a.u.)…”
Section: The Cross Section Image and 3d Reconstruction Of 3d-hie Growmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Advances in tissue engineering enable the development of 3D constructs that are generally less expensive than animals, more reproducible and easy to develop while they provide a more realistic structure, cell-cell, cell-ECM spatial interactions and a more realistic distribution of environmental parameters within the system, such as nutrients and oxygen, chemotherapeutic diffusion, and irradiation deposition as compared to 2D systems. 8,[30][31][32][33][34][35][36] Current 3D in vitro systems of pancreatic tumours include (i) spheroid/organoid systems, [37][38][39][40][41][42][43][44][45] (ii) hydrogel scaffolds 42,[46][47][48] and (iii) polymeric scaffolds. [49][50][51] For example, Ware et al have developed pancreatic cancer spheroids with a distinct cohesiveness of the cellular masses.…”
Section: Introductionmentioning
confidence: 99%